Vitamin D3 – does it correlate with exercise tolerance in stable COPD? - Hassan, Samia; Ali, Taskina; Bennoor, Kazi Saifuddin; Hossain, Md Ali; Rahman, Mustafizur; Khan, Mohammad Abdus Shakur; Rosy, Sharkia Khanam; Nahar, Salsa Bil; Mahmood, Maksuda Binte (Journal of Bangladesh Society of Physiologist, 2019)
Background: Though the classic function of vitamin D3 in skeletal health is established, but its new role has been discovered in tissues and organs other than bones. Vitamin D3 deficiency has been found in patients with various morbid conditions, such as cardiovascular diseases, autoimmune diseases, infectious diseases, Diabetes mellitus and malignancies including respiratory ailments. Objectives: This cross sectional study was designed to evaluate the status of this fat soluble vitamin D3 and its correlation with exercise tolerance in stable COPD patients. Methods: For this purpose, 47 male, smoker (>4 pack years), stable (who has not experienced any acute exacerbation, hospitalizations, urgent care visits, or changes in routine medications within 4 weeks prior to study), COPD patients (post bronchodilator FEV1/FVC<0.70; duration >4 years) of >40 years of age, were selected from the Out Patient Department of National Institute of Diseases of Chest and Hospital (NIDCH), Dhaka. For the assessment of vitamin D3 status, their serum 25-hydroxycholecalciferol [25(OH)D], for exercise tolerance, 6 min walk distance [6MWD; by 6 min walk test], peripheral capillary oxygen saturation (SpO2) [by pulse oximetry], level of dyspnea and fatigue [by Modified BORG scale], were measured. The data were expressed as percentage and mean ±SEM and were statistically analyzed by Pearson’s correlation coefficient test, where p<0.05 was accepted as significant. Results: Out of 47 stable COPD patients, 46 (97.8%) were with serum 25(OH) D < 30 ng/ml. In addition, 6MWD was positively (p£0.05) and dyspnea (p£0.001) along with fatigue (p£0.05) score were negatively correlated with serum 25(OH)D level in these stable COPD patients. Conclusion: This study result concluded that, majority patients with stable COPD had D3 deficiency and this D3 deficiency showed significant correlation with decrement of exercise tolerance. J Bangladesh Soc Physiol. 2019, June; 14(1): 14-20